2020
DOI: 10.1021/acsnano.9b09964
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime and Stability of Silicon Nitride Nanopores and Nanopore Arrays for Ionic Measurements

Abstract: Nanopores are promising for many applications including DNA sequencing and molecular filtration. Solid-state nanopores are preferable over their biological counterparts for applications requiring durability and operation under a wider range of external parameters, yet few studies have focused on optimizing their robustness. We report the lifetime and durability of pores and porous arrays in 10 to 100 nm-thick, low-stress silicon nitride (SiN x ) membranes. Pores are fabricated using a transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 49 publications
6
83
0
Order By: Relevance
“…51 However, several other dielectric membranes have also been used. For example Al 2 O 3 , 52,53 HfO 2 , 54 and TiO 2 55 have been used to improve the nanopore surface charge, pore stability, and membrane photoluminescence respectively. Two-dimensional membranes such as graphene, 56,57 MoS 2 , 58 hBN, 59 WS 2 60 and MXenes, 61 have also received attention for nanopore applications.…”
Section: Solid State Nanoporesmentioning
confidence: 99%
See 1 more Smart Citation
“…51 However, several other dielectric membranes have also been used. For example Al 2 O 3 , 52,53 HfO 2 , 54 and TiO 2 55 have been used to improve the nanopore surface charge, pore stability, and membrane photoluminescence respectively. Two-dimensional membranes such as graphene, 56,57 MoS 2 , 58 hBN, 59 WS 2 60 and MXenes, 61 have also received attention for nanopore applications.…”
Section: Solid State Nanoporesmentioning
confidence: 99%
“…40,74,97 Drilling nanopores using charged particles can also lead to changes in the fundamental membrane composition which may decrease the pore stability. 54,92 Another technique used to fabricate solid-state nanopores relies on the well-developed nanofabrication techniques of electron beam lithography (EBL) and reactive ion etching (RIE). 40,98,99 Here, nanopores are patterned into an electron sensitive resist using EBL and this pattern is transferred to the membrane via RIE.…”
Section: Solid State Nanoporesmentioning
confidence: 99%
“…Such techniques are employed to monitor size and shape of the nanopore [ 82 , 83 , 84 ], or modify surface properties such as charge or hydrophobicity [ 82 , 83 ]. A good advantage of such a coating is that it can increase the stability of the membrane over time by preventing a slow etching by the electrolyte [ 85 ]. In particular, some studies have shown that the gas phase deposition of HfO 2 has inhibited Si 3 N 4 dissolution [ 86 ].…”
Section: Nanopores and Nanopipettesmentioning
confidence: 99%
“…However, in actual experiments, a great number of solid‐state nanopores tend to expand in salt solution with time. [ 61,133,134 ] As we explore thinner membrane for higher sensitivity, the stability and robustness of solid‐state nanopores should attract more attention in order to achieve commercialization of the device.…”
Section: Durabilitymentioning
confidence: 99%
“…By carefully checking the 2D electron energy loss spectrum (EELS) spatial intensity maps of silicon, nitrogen, as well as oxygen elements from a TEM drilled SiN x nanopore, they concluded the expansion of SiN x membrane is a electrochemistry process, which resembles the erosion of silica in salt sea water. [ 133 ] The conclusion is counterintuitive at first sight, since the SiN x membranes are not expected to be etched in aqueous solutions. [ 136 ] However, they found the illumination of electron beams generated an N‐deficient region or Si/SiO 2 ‐rich region around pore edge with a diameter of 20–30 nm ( Figure a), which tend to erode in salt solutions governed by SiO 2 + 2H 2 O ↔ H 4 SiO 4 .…”
Section: Durabilitymentioning
confidence: 99%